A Streamlined Approach to Prader-Willi and Angelman Syndrome Molecular Diagnostics - Strom, Samuel P.; Hossain, Waheeda A.; Grigorian, Melina; Li, Mickey; Fierro, Joseph; Scaringe, William; Yen, Hai-Yun; Teguh, Mirandy; Liu, Joanna; Gao, Harry; Butler, Merlin G. (Frontiers in Genetics, 2021)
Establishing or ruling out a molecular diagnosis of Prader-Willi or Angelman syndromes (PWS/AS) presents unique challenges due to the variety of different genetic alterations which can lead to these conditions. Point mutations, copy number changes, uniparental isodisomy (i-UPD) 15 of two subclasses (segmental or total isodisomy), uniparental heterodisomy (h-UPD), and defects in the chromosome 15 imprinting center can all cause PWS/AS. Here, we outline a combined approach using whole exome sequencing (WES) and DNA methylation data with methylation-sensitive MLPA to establish both the disease diagnosis and the mechanism of disease with maximum possible sensitivity given available technology and improved efficiency compared to serial methods. The authors encourage the use of this approach in the clinical setting to confirm and establish the diagnosis and genetic defect which may account for secondary genetic conditions that may be seen in those with isodisomy 15 impacting surveillance and counseling with more accurate recurrence risks. Other similarly affected individuals due to other gene disorders or cytogenetic anomalies such as Rett syndrome or microdeletions would also be identified with this streamlined approach.